HCV eradication in recurrent hepatitis C after liver transplantation normalizes enhanced endothelial activation. (14th September 2021) - Caballero‐Marcos, Aránzazu; Romero‐Cristóbal, Mario; Puerto, Marta; Fernández‐Yunquera, Ainhoa; Dieguez, Lucia; Navarrete, Cristina; Clemente, Ana; Diaz‐Fontenla, Fernando; Catalán, Pilar; Rincón, Diego; López‐Baena, José‐Ángel; Bañares Cañizares, Rafael; et al.
Summary: The increased risk of cardiovascular disease (CVD) conferred by hepatitis C virus (HCV) is especially relevant after liver transplantation (LT), but its mechanism is still not well defined. This study aimed to evaluate the influence of HCV eradication in inflammatory and endothelial activation markers after LT. We evaluated inflammatory (TNF‐alfa, IL‐6, IL‐8, and MCP‐1) and endothelial activation (E‐selectin, ICAM‐1, VCAM‐1, and MMP‐9) markers before and after eradication in 45 LT recipients with HCV infection (LT+/HCV+) and 44 non‐transplanted HCV‐infected patients (LT‐/HCV+). We also considered an additional group of 40 LT recipients without HCV infection (LT+/HCV‐). LT+/HCV+ patients presented a higher endothelial activation status before eradication compared with LT+/HCV‐ patients. However, levels of E‐selectin, ICAM‐1, VCAM‐1, and MMP‐9 were comparable between LT+/HCV+ and LT‐/HCV+ patients before eradication. HCV eradication decreased ICAM‐1 (5466.55 pg/ml vs. 3354.88 pg/ml, P < 0.001) and VCAM‐1 (10456.52 pg/ml vs. 6658.85 pg/ml, P < 0.001) levels in LT+/HCV+ and LT‐/HCV+ patients. Remarkably, HCV eradication restored levels of endothelial activation markers of LT+/HCV+ patients compared with that of LT+/HCV‐ patients. HCV plays a major role in endothelial dysfunction after LT. Furthermore, HCV eradication restores endothelial activation despite the exposure to immunosuppressive therapy. Abstract : This prospective study demonstrates for the first time that HCV eradication is associated with a significant reduction of endothelial activation in liver transplant recipients. Since CVD is one of the most common causes of death after the first year of LT, eradicating HCV may impact long&term survival and should be evaluated in future studies.